Innerarity, D. (2018). Política para perplejos. Barcelona, España: Galaxia Gutenberg - Robles Leal, Alejandro (2020)
In "Politics for the perplexed", Daniel Innerarity presents us with a fairly clear reading of our global reality, pointing out to an issue with which we all may coincide, but that we had not described with such vehemence: we assist to a time in which politics fills us with uncertainty and bewilderment.